2020
DOI: 10.21203/rs.3.rs-72198/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Irinotecan and Oxaliplatin as the First-Line Therapies for Metastatic Colorectal Cancer: A Meta-analysis

Abstract: BackgroundIrinotecan (IRI) and oxaliplatin (Ox) are standard therapeutic agents of the first-line treatments for metastatic colorectal cancer (mCRC). Previous meta-analyses of randomized controlled trials (RCTs) showed that treatment with Ox-based compared with IRI-based regimens was associated with better overall survival (OS). However, these reports did not include trials of molecular targeting agents and did not take methods for the administration of concomitant drugs, such as bolus or continuous infusion o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our analysis of the prognostic factors of unresectable CRLM patients showed that perioperative chemotherapy was a common independent prognostic factor, and the prognosis of UTCLM, UHFLM, and USFLM patients who received perioperative chemotherapy was significantly better than that of patients without perioperative chemotherapy. This did not seem to be an unexpected result, as many studies have shown the positive effect of perioperative chemotherapy on the prognosis of unresectable CRLM [ 81 83 ], especially when mutational status analysis has been used by some guidelines to guide the treatment and prognosis of CRLM [ 84 , 85 ]. Studies showed that not only KRAS, BRAF could guide the identification of CRLM patients who could benefit most from surgical resection [ 80 , 86 ] , but also KRAS, NRAS, BRAF, TP53, MSI, APC, and PIK3CA became important prognostic indexes to guide perioperative chemotherapy in patients with CRLM [ 87 – 91 ], and could guide the selection of further combined targeted therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Our analysis of the prognostic factors of unresectable CRLM patients showed that perioperative chemotherapy was a common independent prognostic factor, and the prognosis of UTCLM, UHFLM, and USFLM patients who received perioperative chemotherapy was significantly better than that of patients without perioperative chemotherapy. This did not seem to be an unexpected result, as many studies have shown the positive effect of perioperative chemotherapy on the prognosis of unresectable CRLM [ 81 83 ], especially when mutational status analysis has been used by some guidelines to guide the treatment and prognosis of CRLM [ 84 , 85 ]. Studies showed that not only KRAS, BRAF could guide the identification of CRLM patients who could benefit most from surgical resection [ 80 , 86 ] , but also KRAS, NRAS, BRAF, TP53, MSI, APC, and PIK3CA became important prognostic indexes to guide perioperative chemotherapy in patients with CRLM [ 87 – 91 ], and could guide the selection of further combined targeted therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Oxaliplatin-containing regimens, such as FOLFOX (16,17) or XELOX (18,19) and irinotecan-containing regimens, such as FOLFIRI (20)(21)(22) and XELIRI (23)(24)(25), have both been established equally effective in terms of progression-free and overall survival as first-line palliative systemic therapy in mCRC (26). Oxaliplatin-containing regimens may be preferred over irinotecan-based regimens as first-line therapy in mCRC due to their slightly more favourable median overall survival and toxicity profiles (21,27,28), including in elderly patients (29).…”
Section: Introductionmentioning
confidence: 99%